EKSISTENSI HUKUM ADAT MINANGKABAU DALAM PENERAPAN SANKSI DENDA TERHADAP PELAKU ZINA DI NAGARI LIMO KAUM KECAMATAN LIMA KAUM - Alfadrian Alfadrian; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia is a legal state (rechtstaat) in which every legal provision rests or is guided by thePancasila and the 1945 Constitution, because a regulation must not conflict with higher regulations becauseit applies nationally. But in community life besides the existence of national laws there are also customarylaws in the midst of these communities which are born of habits and behavior that develop into what iscalled adat. This custom or habit will later become a provision called customary law. Whereas customarylaw and customary law are still used by certain local communities, especially in the Kenagarian Limo KaumLima Kaum area whose people still use customary criminal law to settle customary criminal acts, especiallyzina crimes. The purpose of writing this thesis is: first, how is the existence of the application of finessanctions against adulterers in Nagari Limo Kaum Lima Kaum Subdistrict, secondly, What is the position ofcustomary criminal law against law enforcement and its practice in Nagari Limo Kaum Lima KaumDistrict.This type of research is using sociological research methods because this research authors directlyconduct research on the location or place to be studied in order to provide a complete and clear picture ofthe problem to be studied. This research was conducted at Nagari Limo Kaum sub-district Lima Kaum ,Tanah Datar District, West Sumatra Province. While the population and samples were all parties related tothe problems examined in this study, data sources used primary data, secondary data and tertiary data,collection techniques the data in this study were interviews and document studies.The conclusions that can be drawn from this study are that the existence of customary criminalsanctions such as being discharged and fined have begun to fade or are rarely used anymore because thepeople in Nagari Limo Kaum are already plural who come and settle so that customary law is not usedanymore and submitted every issue reported to the police. The suggestion that the authors give is that theNagari government and its devices make a Nagari Regulation that regulates customary law or violations ofcustomary law in collaboration with the police and disseminates it to the Nagari Limo Kaum community sothat the Minangkabau customary law persists and will not fade along with the times.Keywords: Existence - Customary Law - Customary Penalty – Adultery